2014
DOI: 10.3109/02699052.2014.919537
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilization following mild traumatic brain injury in female veterans

Abstract: Male Veterans had less outpatient utilization than females in the year following mild TBI diagnosis. Gender and other factors only accounted for a small portion of the differences observed; therefore, gender only partially accounts for differences in healthcare utilization following mild TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Some studies indicate that female veterans are more likely to have depression, or PTSD comorbid with depression, while male veterans are more likely to have PTSD with substance use disorder (Iverson et al, 2011;Pugh et al, 2016). While other studies do not find sex-specific differences in reporting of post-concussive symptoms, or believe it has only a limited influence in the military population (Jackson et al, 2016;Rogers et al, 2014). Given the increasing number of females in military combat and participation in contact sports, concerns about women's health following a mTBI have been raised and further research is warranted.…”
Section: The Role Of Sex-differences In Tbimentioning
confidence: 98%
“…Some studies indicate that female veterans are more likely to have depression, or PTSD comorbid with depression, while male veterans are more likely to have PTSD with substance use disorder (Iverson et al, 2011;Pugh et al, 2016). While other studies do not find sex-specific differences in reporting of post-concussive symptoms, or believe it has only a limited influence in the military population (Jackson et al, 2016;Rogers et al, 2014). Given the increasing number of females in military combat and participation in contact sports, concerns about women's health following a mTBI have been raised and further research is warranted.…”
Section: The Role Of Sex-differences In Tbimentioning
confidence: 98%
“…In addition, when adjusting for demographics and blast exposure, women reported significantly more severe neurobehavioral health symptoms than the men (Iverson et al, 2011). In an examination of VHA health care utilization among OEF/OIF/OND veterans with TBI, Rogers and colleagues (2014) found that women used more outpatient care relative to men in the year following TBI diagnosis. Demographic (i.e., race) and health (i.e., burden of illness) factors were found to account for only a small portion of the gender differences observed; therefore, the authors concluded that other factors in women’s lives that were not examined in the study are contributing to increased health care utilization among female OEF/OIF/OND veterans with TBI.…”
mentioning
confidence: 99%